Comparing vaccination hesitancy in Polish migrant parents who accept or refuse nasal flu vaccination for their children. Issue 13 (17th March 2020) - Gorman, D.R.; Bielecki, K.; Larson, H.J.; Willocks, L.J.; Craig, J.; Pollock, K.G.
Abstract: This study investigates the background to low uptake of nasal influenza vaccination in Polish pupils in Edinburgh, Scotland. In autumn 2018, one week after their child's nasal flu vaccination sessions, 365 Polish parents were sent a questionnaire exploring influences on their vaccination choices. The questionnaire included a series of 10 vaccine hesitancy questions recommended by the WHO SAGE Working Group on Vaccine Hesitancy. 128 questionnaires were returned representing 43.4% of vaccinated, 41.9% of refusing and 23.8% of non-consent form returning parents. Responses highlighted concerns about side effects, new vaccines and the accuracy of professional advice and information sources. There was complacency expressed about vaccination against diseases that are not common any more. Vaccine refusers were consistently more negative about all aspects vaccination and more likely to answer 'don't know'. Almost half of refusers were uncertain about the quality of health information offered to them. Polish migrants in Scotland come with their beliefs about vaccination and modify these as they acculturate to the UK system. They also continue to be influenced by developments and opinions, norms and values from their home country, as well as diaspora media. We have highlighted issues of concern among Polish migrants as a group and gained additional insights by comparing responses of parents who have refused or accepted vaccination. These insights can inform and target messages and strategies to build confidence and encourage immunisation, which should lead to improved vaccine uptake among ethnic population groups.